2011
DOI: 10.1017/s000711451100403x
|View full text |Cite
|
Sign up to set email alerts
|

No effect of 12 weeks' supplementation with 1 g DHA-rich or EPA-rich fish oil on cognitive function or mood in healthy young adults aged 18–35 years

Abstract: The n-3 PUFA are a unique class of fatty acids that cannot be manufactured by the body, and must be acquired via dietary sources. In the UK, as well as in other Western nations, these 'essential' fatty acids are consumed in quantities that fall below government guidelines. The present study explored the effects of 12 weeks' dietary supplementation with 1 g/d of two types of fish oil (FO; DHA-rich and EPA-rich) in 159 healthy young adults aged 18 -35 years. An assessment of performance on a battery of computeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 39 publications
4
82
1
Order By: Relevance
“…Results from RCTs in healthy individuals have shown varied effects of ω-3 FA supplementation (up to 12 weeks) on cognitive function and mood [37,38,47], and a 6-week intervention including ω-3 FA significantly reduced fatigue in patients with lung cancer [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from RCTs in healthy individuals have shown varied effects of ω-3 FA supplementation (up to 12 weeks) on cognitive function and mood [37,38,47], and a 6-week intervention including ω-3 FA significantly reduced fatigue in patients with lung cancer [48].…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines suggest that doses up to 3g per day of marine derived ω-3 FAs are safe [36]; a high EPA:DHA ratio is thought to be preferable [27,37,38 Participants in all groups were contacted by the researcher (AM) via telephone or email on six occasions during the intervention, a week following commencement of the interventions and then approximately every two weeks. Topics of conversation covered their well-being, whether they were taking the capsules as instructed, and the occurrence of any adverse effects.…”
Section: Description Of Interventionsmentioning
confidence: 99%
“…Omega-3 fatty acid supplementations containing EPA and DHA in varying amounts have been reported to improve visual attention and information processing speed in some (Fontani et al 2005(Fontani et al , 2009) but not all (Antypa et al 2009;Jackson et al 2012) studies. De Groot et al (2007) found higher levels of AA were associated with a faster learning curve on the Stroop task measuring general speed of information processing; however, the opposite was found with DHA.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Weigl sorting test (36) , peg-and-ball task, Wisconsin card sort task (32) Comprehension knowledge -Visual processing Rey -Osterrieth complex figure (copy), Rey -Osterrieth complex figure (recall), copy of simple drawings (36) Auditory processing -Short-term memory Immediate word recall (28) ; immediate word recall, digits forward, digits backward, letter -number sequencing (37) ; immediate word recall, N-back, Corsi blocks span, letter -number sequencing (38) ; immediate word recall, spatial working memory, numeric working memory (24) ; memory of digits, memory of story, selective attention test (35) ; N-back (34) ; immediate word recall, digit span, verbal span, Corsi test (36) ; Corsi blocks task, N-back task, numeric working memory (31) ; N-back task (32) ; immediate free recall (33) ; immediate word recall, Corsi blocks task, N-back task, numeric working memory, alphabetic working memory, telephone number working memory task (30) Long-term storage/retrieval Delayed word recall, delayed recognition memory, verbal fluency, Boston naming task (37) ; delayed word recall, delayed word recognition, delayed picture recognition (38) ; delayed word recall, delayed picture recognition, delayed word recognition (24) ; delayed word recall (28) ; delayed word recall, short story test, phonological fluency, semantic fluency (36) ; delayed free recall (33) ; delayed word recall, delayed word recognition, delayed picture recognition, names-to-faces recall, verbal fluency (30) …”
Section: Fluid Reasoningmentioning
confidence: 99%
“…Trail making task composite score of A and B, Stroop task (37) ; finding A's task, digit vigilance, Stroop task (38) ; digit vigilance (24) ; RVIP (28) ; Stroop task (33) ; trail making part A and B (33) ; Stroop task, RVIP, serial 7 subtraction (31) ; Stroop task (32) ; serial 3 subtraction, serial 7 subtraction, RVIP, Stroop task (30) Reaction/decision speed Choice RT (38) ; simple RT, choice RT (24) ; Jensen's decision time two, four and eight choice (28) ; simple RT, two-choice RT, four-choice RT (31) ; simple RT, two-choice RT, four-choice RT (30) Quantitative knowledge -Reading/writing -Unclassified tests MMSE, attentive matrices (36) ; MMSE (29) are going to be statistically combined to create the broader factor. Simply adding task scores together can result in factors that are biased towards one particular cognitive test.…”
Section: Processing Speedmentioning
confidence: 99%